(3GdQSGdI GdefXeI aj aVGFd ecI GdeYXeIs - (3GdfbTHfOj GdNGdOj GdOGZSJGfj, Ndjd MeOjs
(3ChdgG (B:s
(3GdMeO ddg eYdj GdMb heYdfg aGdhGLH YdjfG Cf fMeOg SHMGfg hJYGdi Ydi Cfg LYd dfG hWfG heScfG aj HdOJg GdWjHI hhLgfG Edi HjJg GdMQGe GdPj UGQg bHdI dYGeI GdCeI GdeQMheI hfSJcKQg s
(3BNQgG (B:s
(3ajbhd Cgd GdLfI GfWdbhG HfG ffXQ Edi GdeJMGHjf aj Gddg aEPG CTQahG Ydjge CVGFJ hLhgge ceG JVjA GdTeS Ydi Cgd GdOfjG Ydjge KjGH NVQ ef SfOS ecJhH Ydi LHGgge gDdGA eJMGHhf aj Gddg hGdeJRGhQhf JeJs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs